Socialist City in a Post-Socialist Condition: The History of Transition - Marozas, Martynas (ZARCH, 2015)
Decentralization and shift to market-driven planning systems that started after the fall of USSR all over Central and Eastern Europe, had followed a predetermined path, however it varied depending on socioeconomic and spatial features of a specific location. This paper analyses socialist housing history, its politics, planning culture, institutions, concepts, and ideals that shaped socialist city and its infrastructure in USSR and in Lithuania. It juxtaposes socialist planning principles, construction volume and ideals behind the concept of microrayon, to its actual quality, poor implementation patterns and prevalent underdevelopment culture. Furthermore the paper covers the origins of a legitimacy crisis that Lithuanian planning system entered after independence together with processes and their outcomes that shaped Lithuanian cities during first decade of an independence. Lastly, this paper offers an explanation for chaotic post-socialist transition during and after the “wild east” phase highlighting planning flaws, socio-economic changes in the society, planning incompatibilities and other challenges that Lithuania faced after the shift from planned to a market-driven economy